HIV Infection and Compromised Mucosal Immunity: Oral Manifestations and Systemic Inflammation - Heron, Samantha E.; Elahi, Shokrollah (Frontiers in Immunology, 2017)
Mucosal surfaces account for the vast majority of HIV transmission. In adults, HIV transmission occurs mainly by vaginal and rectal routes but rarely via oral route. In contrast, pediatric HIV infections could be as the result of oral route by breastfeeding. As such mucosal surfaces play a crucial role in HIV acquisition, and spread of the virus depends on its ability to cross a mucosal barrier. HIV selectively infects, depletes, and/or dysregulates multiple arms of the human immune system particularly at the mucosal sites, and causes substantial irreversible damage to the mucosal barriers. This leads to microbial products translocation, and subsequently hyper-immune activation. Although introduction of antiviral therapy (ART) has led to significant reduction in morbidity and mortality of HIV-infected patients; viral replication persists. As a result, antigen presence and immune activation are linked to “inflammaging” which attributes to a pro-inflammatory environment and the accelerated ageing process in HIV patients. HIV infection is also associated with the prevalence of oral mucosal infections and dysregulation of oral microbiota, both of which may compromise the oral mucosal immunity of HIV-infected individuals. In addition, impaired oral immunity in HIV infection may predispose the patients to periodontal diseases which are associated with systemic inflammation and increased risk of cardiovascular diseases. The purpose of this review is to examine existing evidence regarding the role of innate and cellular components of the oral cavity in HIV infection and how HIV infection may drive systemic hyper-immune activation in these patients. We will also discuss current knowledge on HIV oral transmission, HIV immunosenescence in relation to the oral mucosal alterations during the course of HIV infection and periodontal disease. Finally, we discuss oral manifestations associated with HIV infection and how HIV infection and ART influence the oral microbiome. Therefore, unraveling how HIV compromises the integrity of the oral mucosal tissues and innate immune components of the oral cavity and its association with induction of chronic inflammation are critical for the development of effective preventive interventions and therapeutic strategies.